The impact of macroeconomic variables towards economic growth in Malaysia / Muhammad Ammar Bacharuddin - Bacharuddin, Muhammad Ammar (Faculty of Business and Management, 2017)
The aim of this study is to examine factor affecting of economic growth in Malaysia. This paper examines whether the changes trend of the economic growth in Malaysia will give an impact on exports, exchange rate, foreign direct investment and inflation. Over the past few years, the economic growth in Malaysia has experienced difficulty after economic crisis. The study will explain more about the relationship between the economic growth and the independent variables for 30 years. In the process of findings there are few types of analysis were tested using Econometric Views (E-views), such as single linear regression, multiple linear regression, descriptive statistics, unit root tests, and more. The result indicates that there are significantly related to economic growths. This study can be useful for investors, companiesand evengovernment to know which factors that affect gold price in Malaysia.